SISTEM PENGERING HIBRIDA BERBASIS IOT DENGAN PENYIMPANAN PANAS UNTUK OPTIMALISASI ENERGI, KUALITAS PRODUK, DAN REDUKSI DAMPAK LINGKUNGAN TERMAL: ARTIKEL REVIEW - Yunita Djamalu; Romi Djafar; Arifin Matoka (Journal Of Renewable Energy Engineering, 2026)
Post-harvest drying remains a critical point in the agricultural commodity value chain as it determines the rate of moisture loss, physical-chemical quality, microbiological stability, energy consumption, and environmental emissions. In the last decade, the direction of technology development has shifted from passive solar dryers to hybrid drying systems that combine greenhouses, solar collectors, thermal energy storage, auxiliary heat sources, and Internet of Things (IoT)-based monitoring and control. This review article reorganizes and updates the literature on IoT-based hybrid drying systems, focusing on five key dimensions: system architecture, heat storage media, intelligent monitoring and control, drying performance and kinetics, and economic and environmental implications. The synthesis shows that hybrid configurations consistently increase drying chamber temperature, improve heat distribution uniformity, shorten drying time, and maintain product quality compared to open drying or non-hybrid systems. The integration of sensible, latent, or a combination of both has been shown to extend the drying period during periods of decreased solar radiation and stabilize the thermal conditions of the process. At the same time, IoT enables real-time monitoring of temperature, relative humidity, airflow velocity, and equipment safety status, opening the door to more adaptive predictive control. From a sustainability perspective, recent literature shows that hybrid systems can reduce conventional energy consumption, improve exergy indicators, and deliver economic benefits through operational cost savings and potential reductions in carbon emissions. This review emphasizes that future research agendas must move beyond simply increasing drying temperatures to multi-objective optimization that integrates product quality, energy efficiency, control reliability, and environmental impact.